THE IMPORTANCE OF DRAGONFLIES IN ALHAGI PSEUDALHAGI (M. BIEB.) DESV. EX WANGERIN PEST ELIMINATION - Norkobilova , Z.B.; Burieva , X.P; Arabova , N.Z (Actual problems and prospects of the study of the fauna, 2024)
Dragonflies (Odonata), the oldest representatives of the class of insects are predatory insects and are important in biological control in natural processes. This article highlights the importance of dragonflies in the loss of plant aphids (Aphis gossypii).